2013
DOI: 10.1002/cnm.2560
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of non‐Newtonian blood flow and wall shear stress in realistic single, double and triple aorto‐coronary bypasses

Abstract: Considering the fact that hemodynamics plays an important role in the patency and overall performance of implanted bypass grafts, this work presents a numerical investigation of pulsatile non-Newtonian blood flow in three different patient-specific aorto-coronary bypasses. The three bypass models are distinguished from each other by the number of distal side-to-side and end-to-side anastomoses and denoted as single, double and triple bypasses. The mathematical model in the form of time-dependent nonlinear syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
3
17
1
Order By: Relevance
“…Additionally to the analysis of different boundary conditions, the paper also aims to reassess conclusions drawn in the previous study 17 regarding the occurrence of shear‐thinning non‐Newtonian effects in coronary bypasses. The motivation for this part of the paper is the fact that the prospective change in haemodynamics computed for each of the coronary artery outlets will naturally lead to a change in shear‐dependent blood viscosity, which was previously deemed negligible and which now with altered flow conditions will require a re‐evaluation.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally to the analysis of different boundary conditions, the paper also aims to reassess conclusions drawn in the previous study 17 regarding the occurrence of shear‐thinning non‐Newtonian effects in coronary bypasses. The motivation for this part of the paper is the fact that the prospective change in haemodynamics computed for each of the coronary artery outlets will naturally lead to a change in shear‐dependent blood viscosity, which was previously deemed negligible and which now with altered flow conditions will require a re‐evaluation.…”
Section: Introductionmentioning
confidence: 87%
“…As mentioned in the Introduction, the present haemodynamic study is a follow‐up of an earlier work 17 conducted by the authors of this article, which was oriented towards non‐Newtonian blood flow modelling in three patient‐specific aorto‐coronary bypasses. Now with the intent to assess the extent to which the choice of coronary boundary condition can affect the numerical results, let us re‐introduce the three vascular geometries (Figure 3) as representatives of the most often performed standard techniques of coronary artery bypass grafting with the saphenous vein graft.…”
Section: Multiscale Models Of Bypass Haemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed that the Newtonian model returned lower values of wall shear stress and also noted that the use of a non‐Newtonian blood model tended to reduce the predicted peak values of strain rate in the vicinity of the aneurysm. In contrast, Vimmr's study in 2013 of pulsatile non‐Newtonian blood flow in three different patient‐specific aorta‐coronary bypasses indicated that results from the Carreau–Yasuda did not significantly differ from the Newtonian model.…”
Section: Introductionmentioning
confidence: 90%
“…However, the deployed device caused substantial strains and stresses in the arterial wall and plaque that, although not critical in terms of rupture risk, may lead to intimal hyperplasia and restenosis. A treatment option for coronary artery disease typically required once endovascular interventions become insufficient, namely, coronary artery bypass grafting, was the focus of a study presented by Vimmr et al . The long‐term patency of coronary bypass grafts is known to be significantly affected by local haemodynamics.…”
mentioning
confidence: 99%